Conduct disorder: assessment and prescriptive treatment. a case of Zimbabwe - Nyamande, Winifrida S.; Chemhuru, Nyengeterai; Mahlatini, Janet P.; Gudyanga, Ephias (International Journal Advances in Social Science and Humanities, 2016)
The study focused on the counselling of children with conduct disorders in the primary schools. Children with conduct disorders present excessively aggressive and defiant behaviour and have interpersonal problems with teachers, peers, parents and significant others. Such children are usually less responsive to social reinforcement, less empathetic and less understanding of peers’ behaviours. These antisocial behaviours lead to poor adjustment, risk of school failure, membership in deviant peer groups, school drop-out and eventual delinquency. We sought to find out how such children are counselled. Questionnaires and interviews were used as data collecting instruments. The sample comprised of thirty –two educationists. The study established that the educational psychologists had the role of counselling students with special educational needs including those with conduct disorders. They assist schools in the assessment, placement and counselling of such children through the administration of psychological tests to establish the behavioural problems and recommend treatment. It was realised that the implementation of the Guidance and Counselling policy in primary schools was not consistent. Each primary school was carrying out counselling of students in their own way, with others not even aware of the existence of such a policy. The study recommended that the educational psychologists should visit schools frequently and staff develop school heads and teachers on the Guidance and Counselling policy. They should equip teachers with counselling skills to ensure implementation of policy at all levels. Each school should have a counsellor and a counselling room, which would ensure confidentiality and security of children during counselling.